District-energy Planning Method based on Energy Bus System in Hot Summer and Cold Winter Areas - Meng Hua; Wang Hai; Long Weiding (Zhileng xuebao)
A general district-energy planning method that is suitable for hot summer and cold winter areas is proposed in this paper based on an energy bus system (EBS). In the proposed method, multiple thermal or cooling sources and users (buildings) are connected together using warm and cool lines with distributed variable speed pumps (DVSPs). In the new EBS configuration, thermal devices are used to control the water supply temperature in the side of all sources, chillers and heat pumps installed in all users (buildings) are used to provide space cooling, heating, and domestic hot water. Because of the simultaneously decoupled thermal features of the presented EBS configuration, both energy sources and users are capable of adjusting their thermal devices flexibly according to their own local loads. To demonstrate the new district energy planning method, a hydraulic and thermal model is developed, and a case study is illustrated in detail. The results show that combined with the ground source heat pump, water source heat pump, and steam-driven LiBr units, the given method has good efficiency in utilizing low-grade energy resources, with an integrated COP of 3.85 in the summer and 3.17 in the winter.